Comparison of radiological and clinical results of knee intra-articular injections with two ultrasonography-guided approach techniques: A randomized controlled study - Esra Ertilav; Sinem Sarı; Devran Ertilav; Osman Nuri Aydın (Archives of Rheumatology, 2023)
Objectives: The objective of this study was to evaluate the clinical and radiological results of intra-articular injections performed with two different ultrasound-guided approaches in knee osteoarthritis. Patients and methods: The randomized controlled study was conducted on 80 knees of 40 patients (9 males, 31 females; mean age: 63.6±8.2 years; range, 46 to 78 years) with Grade 2-3 gonarthrosis that underwent ultrasound-guided intra-articular injections with suprapatellar (SP) or infrapatellar (IP) approaches between March 2020 and January 2021. After the injection, opaque material spread was fluoroscopically observed. Before the procedure and at the one and three months after the procedure, patients’ Visual Analog Scale (VAS) scores for pain and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores for functional recovery were recorded. Results: In both techniques, one- and three-month VAS and WOMAC scores were found to be significantly lower (p<0.001 and p<0.001, respectively). Of the patients with positive opaque spread, 63.3% were in the IP technique group, and 36.7% were in the SP technique group (p=0.003). In 69.2% of those with radiologically positive opaque spread, the VAS score was significantly higher with >50% regression (p=0.04). In the IP technique, >50% regression rate of the VAS was 86.7% in patients with positive opaque spread, while VAS regression was significantly higher than those without opaque spread (p=0.02). Conclusion: Although the IP approach shows an early-positive opaque transition due to its proximity to the joint, both approach techniques are clinically effective under ultrasound guidance.